Seventh Addenda to Criticism of the Current Science in the World - Pejman Malekinejad, (IJRDO - Journal of Social Science and Humanities Research, 2020)
In this article some scientific problems of Iran were reviewed. My own problems and honors were also mentioned. It was concluded that Iran and I will not become anything in the science, I have no intelligence and Iran and I will not become anything in general. Therefore, according to the principles of DEPRESSIVE REALISM, I must always be happy. Also it was deduced that the only way for the advancement and development of Iran is to make Iran as a state of USA.